Artificial intelligence voice gender, gender role congruity, and trust in automated vehicles - Qiaoning Zhang; X. Jessie Yang; Lionel P. Robert (Scientific Reports)
Abstract Existing research on human–automated vehicle (AV) interactions has largely focused on auditory explanations, with less attention to how voice characteristics shape user trust. This paper explores the influence of gender similarity between users and AV voices and the role of gender-role congruity rooted in societal stereotypes on cognitive and affective trust in AVs. Findings reveal that gender-role congruity moderates the relationship between gender similarity and trust. When an AV’s voice gender aligns with its expected role, gender similarity enhances cognitive and affective trust. However, when gender roles were not congruent, the trust-enhancing effect of gender similarity diminishes. These findings highlight the importance of considering gender in AV voice design for conveying critical driving information and reveal how societal stereotypes shape AV design. The study offers insights for enhancing user trust and acceptance of AV technology, suggesting future research directions for developing AV systems that avoid reinforcing social biases.